1991
DOI: 10.1143/jjap.30.l981
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Madelung Potential in R2-xCexCuO4-δ (R=Pr, Nd, Sm, Eu and Gd) System

Abstract: Powder X-ray diffraction measurements were taken in the R2-x Ce x CuO4-δ (R=Pr, Nd, Sm, Eu and Gd) system. Rietveld refinement of these structures was performed assuming that the space group was 14/mmm. The lattice constant and rare earth metal location were determined to study the electrostatic effects of T'-phase materials. We found that the difference in the Madelung site potential, ΔV (V R-V Cu), as well as T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…The widely accepted positive sign of the charge carriers in La 2Ϫ␤ Sr ␤ CuO 4 is to be contrasted with the situation in Nd21-4 and its homologues, where the sign of the carriers is controversial, 111 with a majority of authors following the original suggestion of Tokura et al 27 that electrons carry the charge in the Nd21-4 homologues. However, the Nd21-4 homologue fabricated with the most careful oxygen control is Pr 2Ϫz Ce z CuO 4 , 24 and the evidence is strong that this robust superconductor is p-type.…”
Section: A La 2؊␤ Sr ␤ Cuomentioning
confidence: 98%
See 2 more Smart Citations
“…The widely accepted positive sign of the charge carriers in La 2Ϫ␤ Sr ␤ CuO 4 is to be contrasted with the situation in Nd21-4 and its homologues, where the sign of the carriers is controversial, 111 with a majority of authors following the original suggestion of Tokura et al 27 that electrons carry the charge in the Nd21-4 homologues. However, the Nd21-4 homologue fabricated with the most careful oxygen control is Pr 2Ϫz Ce z CuO 4 , 24 and the evidence is strong that this robust superconductor is p-type.…”
Section: A La 2؊␤ Sr ␤ Cuomentioning
confidence: 98%
“…The cations Ba and Cu can assume, at most, the ͑integral͒ charge-states Ba ϩ2 and Cu ϩ2 . The rare-earths are R ϩ3 ͑Tables I and II [38][39][40] ͒, leaving a total of 13 electrons to charge the 7 oxygen anions: Based on ionization potential data 40 and Madelung potential calculations 27,41 such as those in Table I, the first of the cations to be further ionized would be Cu ϩ2 →Cu ϩ3 , but nuclear magnetic resonance ͑NMR͒ data show that there is no Cu ϩ3 in YBa 2 Cu 3 O 7 ͑and presumably there is none in Nd123-7 either͒, 42 and point-ion-model calculations show that none of the Cu sites has a Madelung potential as large as the Cu ϩ2 →Cu ϩ3 ionization potential. Indeed, the Madelung potential is too small in magnitude by at least ϳ10 V. ͑See Table I.͒ Therefore a maximum of 13 electrons can charge at most 6.5 oxygen anions to ϷϪ2͉e͉, leaving ͑in some sense͒ Ϸ0.5 O 0 or Ϸ1.0 O Ϫ1 in each unit cell: hypocharged oxygen, O ϪZ , with ZϽ2.…”
Section: A Prediction Of Which Materials Superconductmentioning
confidence: 99%
See 1 more Smart Citation
“…The end result is the formation of disordered structures, like the impurity phase Sm 2 BaMnCuO 7 , where manganese and copper share a site. For smaller lanthanides, incorporation into the rocksalt layers presumably becomes unfavorable as is illustrated by the existence of the K 2 NiF 4 structure for Ln 2 CuO 4 only for Ln=La (16) and in distorted form; for Ln 2 CuO 4 , Ln=Nd-Gd the T 0 -type structure forms (17).…”
Section: Discussionmentioning
confidence: 99%
“…closed-shell Ce +4 ) [12]. Thus, recognizing that most authors simply assume that Ce is in the Ce +4 charge-state, we took a first step towards computing what the charge state of Ce should be [13][14][15]: by examining a calculation of the Madelung potential at a Ce site by Uzumaki et al [16], we concluded that isolated, substitutional Ce cannot be Ce +4 . In a point-ion model for Nd 2 CuO 4 , those authors computed the electrostatic potential at a site where Ce replaces Nd, and found a potential of magnitude 30 V, far too small to exceed the potential of 37 V required to ionize Ce to Ce +4 [17].…”
mentioning
confidence: 99%